Pengaruh Brand Awareness terhadap Loyalitas Pasien: SebuahTinjauanSistematis - Suci Inda Kurniyah (MAHESA : Malahayati Health Student Journal, 2026)
ABSTRACT Smoking behavior among Indonesian students continues to rise and has become Background: In today's highly competitive healthcare landscape, patient loyalty is recognized as a critical indicator of institutional success. Loyalty extends beyond mere satisfaction, encompassing elements of trust, perceived quality, and patients' willingness to recommend healthcare services to others. This systematic review aims to evaluate the influence of brand awareness on patient loyalty within healthcare settings. A systematic literature review was conducted by searching academic databases including ProQuest, Google Scholar, and PubMed. The search utilized Boolean operators and keywords such as “brand awareness,” “patient loyalty,” “hospital,” and their equivalents in the Indonesian language. Articles published between 2020 and 2025 were considered, with inclusion criteria focusing on peer-reviewed studies available in full text and written in English or Indonesian. The Critical Appraisal Skills Programme (CASP) checklist was applied to assess the quality and relevance of each study. A total of 15 eligible articles were included in the final analysis. The findings indicate that brand awareness significantly influences patient loyalty, both directly and indirectly through mediating variables such as patient satisfaction, trust, and perceived service quality. Additionally, digital marketing strategies and social media engagement were found to be effective in enhancing brand awareness and fostering emotional bonds between patients and healthcare institutions. Brand awareness serves as a strategic foundation in managing long-term patient relationships. Healthcare providers are advised to adopt an integrated approach that combines brand development, quality improvement initiatives, digital marketing, and patient experience management to build and sustain patient loyalty. Keywords: Brand Awareness, Patient Loyalty, Healthcare Services.  ABSTRAK Dalam era persaingan layanan kesehatan yang semakin ketat, loyalitas pasien menjadi indikator penting keberhasilan institusi kesehatan. Loyalitas tidak hanya mencerminkan kepuasan terhadap layanan, tetapi juga berkaitan dengan kepercayaan, persepsi kualitas, dan kecenderungan pasien untuk merekomendasikan layanan. Penelitian ini bertujuan untuk mengkaji secara sistematis pengaruh brand awareness terhadap loyalitas pasien. Metode penelitian menggunakan pendekatan systematic review dengan pencarian artikel dari basis data ProQuest, Google Scholar, dan PubMed menggunakan kombinasi kata kunci “brand awareness”, “patient loyalty”, “hospital”, serta padanan dalam bahasa Indonesia. Setelah proses seleksi dan penilaian kualitas menggunakan CASP checklist, diperoleh 15 artikel yang relevan.  Hasil kajian menunjukkan bahwa brand awareness berperan signifikan dalam membentuk loyalitas pasien, baik secara langsung maupun melalui mediator seperti kepuasan, kepercayaan, dan kualitas layanan. Selain itu, strategi pemasaran digital dan penggunaan media sosial terbukti efektif dalam meningkatkan brand awareness dan memperkuat hubungan emosional pasien terhadap institusi. Pentingnya penguatan brand awareness sebagai fondasi utama dalam strategi manajemen hubungan dengan pasien. Institusi kesehatan disarankan untuk menerapkan pendekatan holistik yang mencakup peningkatan kualitas layanan, pemanfaatan media digital, serta pengelolaan pengalaman pasien untuk mempertahankan loyalitas secara berkelanjutan. Kata Kunci: Brand Awareness, Loyalitas Pasien, Layanan Kesehatan.